The problems of establishing a small business innovation in scientifi c and educational spheres - Sidorenko, E. N. (Journal of Economic Research & Business Administration, 2015)
The estimation of the innovation activity of Kazakhstani companies give reasons for low innovation passivity entrepreneurship in general, small and medium-sized enterprises in particular. The reasons that are not conducive to the emergence and development of small innovative enterprises in Kazakhstan. The modern innovative system has to be harmoniously presented not only the large innovative companies, but also in a large number by the small innovative enterprises. In the developed countries for the last decades value of small enterprises in the innovative sphere grew. Advantages of the small innovative enterprises consist in fl exibility, ability quickly to adapt to new requirements of technical progress. It is especially important in the conditions of deepening of specialization and diversifi cation of production, expansion of product range, a production and demand individualization. The small innovative enterprises master release of small-scale, unique production. With NTP development constantly there are markets of new goods and the services which capacity is insignifi cant at the beginning, doesn’t demand mass production that opens possibilities of growth of small enterprises. Original study was proposed measures to improve public support is small,innovative companies.